The financial burden of malnutrition in hospitalized pediatric patients under five years of age - Kulnipa Kittisakmontri (2018)
© 2016 European Society for Clinical Nutrition and Metabolism Background Under-five children are a medically fragile group which is compromised by hospitalization. Malnutrition in those patients not only increases complications and mortality but also affects hospital resource utilization. Therefore, this study was conducted to clarify the impact of malnutrition on hospital expenditures. Methods This prospective cohort study was performed at a tertiary hospital in Thailand. Under-five children who were admitted to general pediatric wards were included. Demographic data, the length of stay (LOS), and anthropometric measurements at admission were recorded. The classification of wasting and stunting were defined according to the World Health Organization (WHO) classification. Moreover, all hospital expenses were calculated directly based on the actual billing including the total hospital cost, cost of bed, enteral formula, medications, medical apparatus and procedures, nursing care, investigations and surgery. Results One-hundred and five patients with a mean age of 26.8 ± 1.8 months were included. The majority of them were males (61%) with the leading cause of infectious disease. According to the prevalence of malnutrition, the percentage of patients who had only stunting or wasting were 24.8% and 10.5%, respectively while 15.2% of all patients had both stunting and wasting. Regardless of stunting, the wasting patients had a significantly higher cost of bed, enteral formula, nursing care, and medical apparatus. Particularly, the highest costs of all expenditures including the total hospital cost were found in patients who were both stunted and wasting. Apart from the financial burdens, the wasting patients stayed longer in the hospital and the LOS also significantly correlated with the total hospital cost (r = 0.84, p = 0.01). Conclusions The present study underscores the high prevalence of malnutrition in under-five pediatric patients. The malnourished patients, in particular the wasting group, had longer LOS and consequently had increased hospital expenses.